2015
DOI: 10.1186/s40885-016-0042-0
|View full text |Cite
|
Sign up to set email alerts
|

A review on prescribing patterns of antihypertensive drugs

Abstract: Hypertension continues to be an important public health concern because of its associated morbidity, mortality and economic impact on the society. It is a significant risk factor for cardiovascular, cerebrovascular and renal complications. It has been estimated that by 2025, 1.56 billion individuals will have hypertension. The increasing prevalence of hypertension and the continually increasing expense of its treatment influence the prescribing patterns among physicians and compliance to the treatment by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
78
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(94 citation statements)
references
References 35 publications
4
78
2
10
Order By: Relevance
“…In particular, exposure assessments differed between the studies, including the year of the assessment. Practice patterns and treatment strategies for hypertension have changed over time [65]. We tried to address this situation by stratifying patients according to year of interview, prior to 2003 compared to 2003 and thereafter, when the guidelines for prevention and management of hypertension had changed [53].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, exposure assessments differed between the studies, including the year of the assessment. Practice patterns and treatment strategies for hypertension have changed over time [65]. We tried to address this situation by stratifying patients according to year of interview, prior to 2003 compared to 2003 and thereafter, when the guidelines for prevention and management of hypertension had changed [53].…”
Section: Discussionmentioning
confidence: 99%
“…Antihypertensive medications are major culprits for GT [ Table 5]. It is estimated that more than one billion adults are hypertensive worldwide, which is projected to increase to 1.56 billion by the year 2025 (36). These findings support the notion that dentists should be aware of possible oral ADRs.…”
Section: Resultsmentioning
confidence: 83%
“…We observed a 48% reduction in ACEi/ARB use in the post‐JNC‐8 era compared with the earlier period. This pattern contrasts with JNC‐8 recommendations for the general population and with observation that ACEi/ARB use has increased in general population . The difference may relate to specific considerations or concerns in KTx recipients.…”
Section: Discussionmentioning
confidence: 99%
“…As in the general population, CCB use appears to have increased in recent years . A study directly comparing ACEi to CCB use in KTx recipients showed similar safety and efficacy; however, CCBs were associated with improved GFR 2 years post‐transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation